2015
DOI: 10.1002/ccd.25891
|View full text |Cite|
|
Sign up to set email alerts
|

Embolization of left atrial appendage closure devices: A systematic review of cases reported with the watchman device and the amplatzer cardiac plug

Abstract: LAA closure device embolization occurs mainly in the periprocedural period but late embolizations are not uncommon. Although embolization into the aorta or the left atrium can be successfully managed by percutaneous techniques in most cases, device embolization into the LV is associated with a higher rate of surgical retrieval, increasing thereby procedure-related morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 23 publications
(27 reference statements)
1
64
0
Order By: Relevance
“…Several possible complications have been reported after LAA closure such as pericardial effusion, free wall rupture and device thrombosis [3][4][5]. Device embolization is a known complication with an average reported rate of less than 4 % [6]. However, in a current meta-analysis late embolization of Amplatzer cardiac plug (ACP) was reported in 6 cases and were mainly clinically asymptomatic and detected during routine echocardiography [6].…”
Section: Introductionmentioning
confidence: 92%
“…Several possible complications have been reported after LAA closure such as pericardial effusion, free wall rupture and device thrombosis [3][4][5]. Device embolization is a known complication with an average reported rate of less than 4 % [6]. However, in a current meta-analysis late embolization of Amplatzer cardiac plug (ACP) was reported in 6 cases and were mainly clinically asymptomatic and detected during routine echocardiography [6].…”
Section: Introductionmentioning
confidence: 92%
“…[3][4][5] The potential mechanisms leading to device embolization include incorrect device apposition, device undersizing or excessive oversizing, shallow landing zone, vigorous tug test, and others. In particular, a morphologically early lobulated LAA can cause a relatively shallow landing zone for device implantation, which may contribute to device dislodgement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Percutaneous retrieval of the embolized device in the LV is very challenging due to the substantial risk of damage to the aortic and mitral valves, even though a dislodged device is relatively stable in position. Stabilizing wires, especially in the unfolded state of the embolized device, may hook into surrounding structures, such as the mitral valve, causing tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review by Aminian et al, two-thirds of reported cases were acute, with 60% of those cases occurring during the procedure. Most cases were asymptomatic [55]. Device embolization may be diagnosed by fluoroscopy, chest X-ray, TTE, TOE or CCTA (Fig 7, panel C).…”
Section: Complicationsmentioning
confidence: 99%